(untitled) (Research, Society and Development, 2022)
Cardiac surgery is a highly complex procedure, performed on the heart or large vessels, being performed by a specialized professional, such as the surgeon. The objective was to carry out a literature review seeking to synthesize the main clinical evidence on the effectiveness of regional blocks in anesthesia for cardiac surgeries. This is an integrative review, in which the search for articles was carried out in the following databases: LILACS; SCIELO and PUBMED, between the years 2016 to 2021, which made it possible to identify and select 11 research. The results revealed that regional blocks in anesthesia for cardiac surgery are, for the most part, safe, with little risk of complications and great efficacy. However, Serratus anterior plane block, PECS II or intercostal nerve block groups can bring complications related to infection, pneumothorax and local anesthetic toxicity due to the larger volume of injection needed and bilateral erector spinae plane block is not safe. in patients on chronic use of antiplatelet agents, intraoperative systemic anticoagulation and cardiopulmonary bypass-induced coagulopathy, the main complications being related to the use of regional blocks in anesthesia for cardiac surgeries. Therefore, future research should focus on establishing dosing regimens for specific blocks in their different planes in cardiac surgery to assess their efficacy, safety and mechanisms of new blocks, as well as safety of liposomal bupivacaine and other adjuvants for latter indications.